2004
DOI: 10.1309/qqlfqu88xk435epy
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unsuspected PNH-Type Cells in Flow Cytometric Immunophenotypic Analysis of Peripheral Blood and Bone Marrow

Abstract: In this report, the flow cytometric expression patterns for CD14 on monocytic cells and CD16 on granulocytic cells in peripheral blood or bone marrow specimens are illustratedfor 15 patients proven to have a paroxysmal nocturnal hemoglobinuria (PNH) phenotype by flow cytometric analysis for CD55 and CD59. The varied clinical manifestations of PNH and its rarity may make it difficult to recognize clinically. As a result, blood or bone marrow samples may be submitted for flow cytometric analysis to exclude bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Validation of this BM‐method revealed similar results in comparison with PNH‐analysis in PB and in paired blood and BM samples. Our findings demonstrated that PNH assessments can be achieved in BM samples of cytopenic patients, though most reliably in the mature neutrophil compartment because of higher sensitivity as compared to the lower frequent monocyte subset, thereby confirming data from previous reports (Dulau‐Florea et al, 2018; Nakakuma et al, 1995; Olteanu et al, 2006; Thomason et al, 2004; Yang et al, 2013). In our hands, 0.1% was the most reliable cut‐off.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Validation of this BM‐method revealed similar results in comparison with PNH‐analysis in PB and in paired blood and BM samples. Our findings demonstrated that PNH assessments can be achieved in BM samples of cytopenic patients, though most reliably in the mature neutrophil compartment because of higher sensitivity as compared to the lower frequent monocyte subset, thereby confirming data from previous reports (Dulau‐Florea et al, 2018; Nakakuma et al, 1995; Olteanu et al, 2006; Thomason et al, 2004; Yang et al, 2013). In our hands, 0.1% was the most reliable cut‐off.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In RDD, the histiocytes typically stain positive for S100 and CD68 and negative for CD1a [18–21]. These features with the absence of eosinophils and Birbeck's granules on electron microscopy make the differential diagnosis with CNS Langerhans Cell Histiocytosis (LCH) possible [18, 22, 23]. Another interesting differential diagnosis is Erdheim-Cester Disease (ECD), which is a rare non-Langerhans histiocytic disorder most commonly characterized by multifocal osteosclerotic lesions of the long bones.…”
Section: Discussionmentioning
confidence: 99%
“…21 Thomason and colleagues recommend the addition of CD 14 (monocytes) and CD16 (granulocytes), which are routine FCM markers, to CD 55 and CD 59, and to search for abnormal expression of CD 14 and CD 16 for increased PNH sensitivity. 22 Similarly, Hernandez-Campo and colleagues recommend CD 16/CD 24/CD 55/CD 59/CD 66b/ CD 157 as a neutrophil panel; CD 14/CD 55/CD 157 for monocytes; CD 24/CD 48/CD 52/CD 55 for B cells; CD 48/CD 52/CD 55 for CD 4 (+) T cells; CD 55/CD 59 for eosinophils; and CD 48/CD 55 for CD 8 (+) T cells. If limited to 1 marker: CD 48 for CD 56 (low) NK cells; CD 55 for BOCA 3(-) dendritic cells plus CD 56 (high) NK cells; and CD59 for RBCs.…”
Section: Flow Cytometric Monoclonal Antibody Eramentioning
confidence: 99%